The impact of fixed appliances (Braces) on quality of lifes - Azrul Hafiz Abdul Aziz; Atiqah Jamal; Nurazfalina Azura; Rahimah Sahudi; Murshida Marizan No (University of Dicle, 2024)
Indexed by Scopus